Where heaven and earth meet: the spiritual in the art of Kandinsky, Rothko, Warhol, and Kiefer - Stoker, Wessel (Currents of encounter, 2012)
Art has always been important for religion or spirituality. Secular art displayed in museums can also be spiritual, and it is this art that is the subject of this book. Many of the works of art produced by Wassily Kandinsky, Mark Rothko, Andy Warhol, and Anselm Kiefer are spiritual in nature. These works reveal their own spirituality, which often has no connection to official religions. Wessel Stoker demonstrates that these artists communicate religious insights through images and shows how they depict the relationship between heaven and earth, between this world and a transcendent reality